Space and self in early modern European cultures - Sabean, David Warren; Stefanovska, Malina (UCLA Clark Memorial Library Series, 2012)
"The notion of 'selfhood' conjures up images of self-sufficiency, integrity, introspectiveness, and autonomy - characteristics typically associated with 'modernity.' The seventeenth century marks the crucial transition to a new form of 'bourgeois' selfhood, although the concept goes back to the pre-modern and early modern period. A richly interdisciplinary collection, Space and Self integrates perspectives from history, history of literature, and history of art to link the issue of selfhood to the new and vital literature on space